Stigma terhadap pasien pasca COVID-19 dan faktor yang mempengaruhinya - putri, intan okrima (Jurnal Cakrawala Promkes, 2021)
Stigma is a negative action that can reduce a person’s self-confidence. During the COVID-19 pandemic, the stigma can be in the form of refusal of bodies, expulsion of medical staff or ex-communication of patients with confirmed COVID-19 and post-COVID-19 patients. There are 2 Post-COVID-19 patients in Papringan Hamlet. This study aims to find out the influence of knowledge, attitudes, and role of community leaders on the stigma against Post-COVID-19 patients in Papringan Helmet Sidomukti Magetan Regency. This was a cross-sectional study. The population were the people who live in Papringan Hamlet, the sample amount was 97 respondents who used the Slovin formula. The sample criteria were aged 26-45 years, chosen by purposive sampling technique. Data were collected by questionnaires and checklist observations. Data analysis used the logistic regression test. Results: The results of the bivariate analysis test showed that there was an influence a relationship between knowledge (Sig. 0,000), attitude (Sig. 0,000), and roles of community leaders (Sig. 0,000) on the stigma against post-COVID-19 patients and multivariate analysis using Binary logistic test indicated there is an influence of knowledge (OR=16,955) to stigma Post-COVID-19 patients in Papringan Hamlet Sidomukti Magetan Regency. The Health Service and community health centres can eliminate the stigma of Post-COVID-19 patients in the community by increasing public knowledge through health education, as well as encouraging the role of religious leaders and community leaders to influence public attitudes so as not to carry out negative stigma against Post-COVID patients.